THE 17TH-CENTURY JOHANNES HOORNBEECK’S VIEWS ON MISSION, ECUMENISM AND HISTORICAL THEOLOGY AND ITS CURRENT RELEVANCE - J W Hofmeyr (Acta Theologica)
In this second article (cf. Hofmeyr 2016), like the previous one, I would like to introduce Johannes Hoornbeeck and the Further Reformation, besides other goals, to the Anglo-Saxon world. This article focuses primarily on the 17th-century theologian Johannes Hoornbeeck and some of his views within the context of the Further Reformation. I address the issue related to an analysis of Hoornbeeck’s contributions as a missiologist, a theologian with a clear ecumenical and irenical orientation, and a historical theologian. In my opinion, he can be regarded as the second most prominent theologian, besides Gisbertus Voetius. In some respects, Hoornbeeck even surpasses him. This critical overview also focuses on the Further Reformation as an ecclesiastical and theological development.